PENGGUNAAN MODEL THINK PAIR SHARE UNTUK MENINGKATKAN AKTIVITAS BELAJAR MATA PELAJARAN EKONOMI SMAN 1 SUNGAI RAYA - Hetty, Asteria Mey; Sulistyarini, Sulistyarini; Sumartono, Bambang Genjik (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe title of this research use of Think Pair Share models in increasing student learning activities in economic subjects in class XI IPS V SMA Negeri 1 Sungai Raya .The problem in this research is whether using the Think Pair Share model can increase student learning activities in economic subjects in class XI IPS V SMA Negeri 1 Sungai Raya. The research method used was classroom action research with descriptive quantitative research. The data source of this study was students of class XI IPS V and the data were observation sheets of student learning activities and documentation. The results of research on student activities that appear are seen from the student performance indicator sheet that is cycle I with a percentage of 53.05% Category II cycle with a percentage of 71.42% high category so that there is a percentage increase of 18.42% from cycle I to cycle II. Â Keywords: Think Pair Share, Student Learning Activities, Economic Subjects